High Compliance Rates and the Roles of Gender in Hand Hygiene Practices Among Medical Laboratory Technologists at USM Health Campus - Setiyadi, Ain Fatihah; Sabri, Nurhidayah; Samad, Nurul Izzah Abdul; Hasan, Nurul Atikah Che; Yhaya, Mohd Firdaus; Hamzah, Nurul Ainun (Knowledge Dynamics, 2025)
Background: Effective hand hygiene is crucial to prevent laboratory-acquired infections (LAIs), yet research on MLTs' practices remains limited. The study examines hand hygiene compliance and adherence factors among Medical Laboratory Technologists (MLTs) at Universiti Sains Malaysia (USM) Health Campus. Methods: A cross-sectional study involved 125 MLTs, utilising self-administered questionnaires to assess sociodemographic characteristics, knowledge, attitudes, practices (KAP), and access to hand hygiene tools. Descriptive and inferential statistical analyses were performed to identify key compliance predictors. Results: The findings revealed a high compliance rate of 97.6%, with 94.4% of participants reporting good access to hand hygiene resources. Female MLTs demonstrated significantly higher adherence to hand hygiene protocols as compared to their male counterparts (Adj b= 0.222, 95% CI: 0.040, 0.404), while other factors such as age, education, and training did not significantly affect compliance (p>0.05). Conclusion: Despite high KAP scores, these variables did not predict adherence, highlighting the complex interplay of behavioural and systemic factors in hand hygiene practices. Future studies should explore innovative approaches, including direct observational methods, gender-specific initiatives, and organisational strategies to enhance hand hygiene practices further. These efforts are essential to strengthen infection control measures, promote laboratory safety, and improve outcomes for healthcare workers and patients.